2015
DOI: 10.1051/0004-6361/201527046
|View full text |Cite
|
Sign up to set email alerts
|

An extreme [O III] emitter atz= 3.2: a low metallicity Lyman continuum source

Abstract: Aims. Cosmic reionization is an important process occurring in the early epochs of the Universe. However, because of observational limitations due to the opacity of the intergalactic medium to Lyman continuum photons, the nature of ionizing sources is still not well constrained. While high-redshift star-forming galaxies are thought to be the main contributors to the ionizing background at z > 6, it is impossible to directly detect their ionizing emission. Therefore, looking at intermediate redshift analogues (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 191 publications
(167 citation statements)
references
References 132 publications
(234 reference statements)
7
158
2
Order By: Relevance
“…In many respects, the properties of the compact z ∼ 0.3 leaking sources are very similar to those of the z = 3.218 Lyman continuum leaker Ion2 found by Vanzella et al (2015) and de Barros et al (2016). First Ion2 is also bright in the UV, M UV = −21, which is ≈M UV (z = 3).…”
Section: Comparison With the Z = 3218 Lyc Leaking Galaxy Ion2supporting
confidence: 72%
See 1 more Smart Citation
“…In many respects, the properties of the compact z ∼ 0.3 leaking sources are very similar to those of the z = 3.218 Lyman continuum leaker Ion2 found by Vanzella et al (2015) and de Barros et al (2016). First Ion2 is also bright in the UV, M UV = −21, which is ≈M UV (z = 3).…”
Section: Comparison With the Z = 3218 Lyc Leaking Galaxy Ion2supporting
confidence: 72%
“…Furthermore, Ion2 is also a compact source with a size ∼300 ± 70 pc (cf. de Barros et al 2016). Interestingly, the two latter properties are found a posteriori, since the source was selected from a peculiar color selection.…”
Section: Comparison With the Z = 3218 Lyc Leaking Galaxy Ion2mentioning
confidence: 91%
“…In this regard, recent progress has been made in the field of photo-ionization modeling (Jaskot & Oey 2013;Nakajima & Ouchi 2014;Zackrisson et al 2016;Inoue 2011), subsequently confirmed by observations (e.g., de Barros et al 2016;Vanzella et al 2016b;Verhamme et al 2016). In particular, line ratios in the rest-frame optical band like the O32 index ([Oiii]λ5007/[Oii]λ3727) and specific properties of the Lyα profile (Behrens et al 2014;Verhamme et al 2015;Dijkstra et al 2016) can provide valuable indirect probes of the physical state of the interstellar medium and of the column density of neutral gas (e.g., density-bounded or ionization-bounded), as well as the connection with the ultraviolet spectral slope, the Balmer emission lines and the Lyman continuum leakage (Zackrisson et al 2013(Zackrisson et al , 2016.…”
Section: Dynamical Mass Of Id11mentioning
confidence: 73%
“…Very few detections were reported, however, and they show very low escape fractions relative to the UV radiation, of the order of a few percent (Shapley et al 2006;Iwata et al 2009;Siana et al 2010;Nestor et al 2013). More recently, de Barros et al (2015) reported a spectroscopic detection of Lyman continuum emission in a z ∼ 3.2 galaxy with a relative escape fraction 16 of f esc ∼ 65%. Figure 9.…”
Section: Implications For Cosmic Reionizationmentioning
confidence: 99%